Harmonic Mitigation in Inverter Circuits Through Innovative LC Filter Design Using PSIM - Habib Muhammad Usman; Muhammad Mahmud; Sani Saminu; Salihu Ibrahim (Universitas Ahmad Dahlan, 2024)
The increasing use of renewable energy sources, such as solar and wind power, and the growing ubiquity of High Voltage Direct Current (HVDC) transmission systems to improve power transmission efficiency are the main factors behind the increased deployment of inverter circuits. However, high harmonic distortions in the resultant sine wave are a major problem for inverter circuits and could jeopardise circuit efficiency if left unchecked. This study presents a novel, affordable, and effective LC filter intended to remove almost all harmonic content from inverter circuits. The study uses PSIM software to model, design, and control a three-phase inverter. Starting with the DC power supply, the study makes use of effective three-legged IGBT (insulated gate bipolar transistor) semiconductor devices as switch elements due to their high and current rating as well as faster operation. The switching gate pulses that turn inverter switches on and off at regular 60-degree intervals are produced by the pulse controller that controls the switches. This study's results show that the innovative LC filter in the inverter significantly reduced total harmonic distortion (THD) in all phases of the power signal. Specifically, THD decreased from 37.68% to 0.47% in the red phase, from 37.69% to 0.48% in the blue phase, and from 37.71% to 0.48% in the yellow phase. This reduction results in a notable improvement in power quality in all phases of the signal. Additionally, there is a noticeable increase in voltage magnitude, stabilizing and raising levels from 17.92 V to 23.83 V in the red phase, 17.93 V to 23.81 V in the blue phase, and 17.83 V to 23.81 V in the yellow phase due to the LC filter. These results demonstrated the effectiveness of the LC filter-equipped inverter for industrial, HVDC, and renewable energy applications.